2017
DOI: 10.1016/j.ijscr.2017.09.017
|View full text |Cite
|
Sign up to set email alerts
|

Case report of a littoral cell angioma of the spleen and accessory spleens: A benign vascular tumour

Abstract: IntroductionLittoral- cell angioma (LCA) is a rare benign vascular tumour of the spleen. There have been less then 80 cases reported in the literature.Recent reports have described it to be a malignant lesion with congenital and immunologic associations. We report a case of LCA of the spleen.Presentation of caseA 52 -year-old male patient was admitted to hospital with a three month duration of intermittent upper abdominal pain and nausea. Imaging studies, including computer tomography (CT) and magnetic resonan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 8 publications
(8 reference statements)
0
2
0
Order By: Relevance
“…In fact, one patient developed tumor recurrence in the accessory spleen 7 years after undergoing splenectomy, which showed no significant change during the 6-month follow-up ( 16 ). According to our statistics, four patients developed LCA both in the spleen and accessory spleen ( 16 , 43 , 89 , 90 ). Therefore, it was quite reasonable to find a recurrence of LCA on the unresected accessory spleen.…”
Section: Resultsmentioning
confidence: 91%
“…In fact, one patient developed tumor recurrence in the accessory spleen 7 years after undergoing splenectomy, which showed no significant change during the 6-month follow-up ( 16 ). According to our statistics, four patients developed LCA both in the spleen and accessory spleen ( 16 , 43 , 89 , 90 ). Therefore, it was quite reasonable to find a recurrence of LCA on the unresected accessory spleen.…”
Section: Resultsmentioning
confidence: 91%
“…[4] In addition, it is important that the patient be monitored during the postoperative period to evaluate recurrence or metastasis. [10,11] A study by Bisceglia et al (1998) [12] showed that five of the twenty-one cases studied were associated with other malignancies, thus demonstrating the need for post-surgical follow-up. Postoperative complications can be prevented with prophylactic measures such as patient education, chemoprophylaxis, and immunoprophylaxis.…”
Section: Discussionmentioning
confidence: 96%